A fiber-guided motorized rotation laser scanning thermography technique for impact damage crack inspection in composites - Liu, Haochen; Tinsley, Lawrence; Deng, Kailun; Wang, Yizhong; Starr, Andrew; Chen, Zhenmao; Zhao, Yifan (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Laser Thermography manifests superior sensitivity and compatibility to detect cracks and small subsurface defects. However, the existing related systems have limitations on either inspection efficiency or unknown directional cracks due to the utilization of stationary heat sources. This article reports a Fiber-guided Motorised Rotation Laser-line Scanning Thermography (FMRLST) system aiming to rapidly inspect cracks of impact damage with unknown direction in composite laminates. An optical head with fibre delivery integrated with a rotation motor is designed and developed to generate novel scanning heating in a circumferential rotation manner. A FEM model is first proposed to simulate the principle of FMRLST testing and produce thermograms for the development of post-processing methods. A damage enhancement method based on Curvelet Transform is developed to enhance the visualization of thermal features of cracks, and purify the resulting image by suppressing the laser-line heating pattern and cancelling noise. The validation on three composite specimens with different levels of impact damage suggests the developed FMRLST system can extract unknown impact surface cracks efficiently. The remarkable sensitivity and flexibility of FMRLST to arbitrary cracks, along with the miniaturized probe-like inspection unit, present its potential in on-site thermographic inspection, and its design is promising to push the LST towards.
Keywords: Motorised Rotating Laser-line; Laser scanning thermography; Barely Visible Impact Crack (BVIC); Curvelet Transformation; Composite laminates